(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
With time, as the business environment has become more complex and layered, a significant auxiliary change in the financial systems has become the imbuement of competition. Inside these multi-layered financial systems, there is elevated competition with the rise of new age of family-owned organizations. In this scenario, the significance of HRM becomes even more relevant and profound. In the current environment, it has become obligatory to make HRM as a vital accomplice in this particular sector of the economy, i.e. the family-owned business (FOB) segment. A critical management challenge for this segment today is how to efficiently, effectively and competitively utilize Human Resource.